Capitalism goes care: Elder and child care between market, state, profession, and family and questions of justice and inequality - Aulenbacher, Brigitte; Décieux, Fabienne; Riegraf, Birgit (Equality, Diversity & Inclusion, 2018)
The starting point of the paper is the meteoric rise of care and care work upon the societal and sociological agenda. Referring to Polanyi, the authors argue that this is the manifestation of a new phase of capitalist societalisation (Vergesellschaftung) of social reproduction in the form of an economic shift. The purpose of this paper is to discuss the societal organisation of care and care work and questions of inequality and justice.Design/methodology/approach The first part of the paper illustrates some facets of the economic shift in the field of care and care work. The second part reconstructs the societal organisation of care and care work in the private sector, state, third sector and private households from the mid-twentieth century in the context of questions of inequality and justice. The third part draws on the institutional logics perspective and French pragmatic sociology and the own case studies on home care agencies (HCA), residential care communities (RCC) and early child care (ECC) in Austria and Germany and shows how conflicting demands give rise to new questions of justice. The paper ends with a short conclusion.Findings The paper shows how the commodification and de-commodification of care and care work have changed over time and how the economic shift – illustrated in the case of HCA, RCC and ECC – is accompanied by conflicting demands and questions of justice.Originality/value A Polanyian perspective on the relation between market and society is combined with the neo-institutionalist and pragmatic idea that orientations rooted in the “logics” of the market, the state, the family and the profession influence how conflicting demands in elder and child care are dealt with and how questions of inequality and justice arise.
Sociology
Keywords: capitalism; care work; caring communities and social investment; community health services; countermovement; decommodification; economic systems; elder and child care; home care agencies; home care services; social justice; social reproduction

The economic shift and beyond: Care as a contested terrain in contemporary capitalism - Aulenbacher, Brigitte; Décieux, Fabienne; Riegraf, Birgit (Current Sociology, 2018)
This article argues that we are witnessing a fundamental transformation of capitalism. Under the auspices of an economic shift, social reproduction and constituent care and care work are undergoing a process of reorganization. The first part draws on Karl Polanyi’s analysis of the relation between market and society and on contemporary revisions of his approach. Referring to core arguments from his perspective on the market society it identifies processes of commodification, marketization and quasi-marketization, which we can understand as an economic shift driving the development in the field of care and care work. The second part refers to empirical studies in Austria and Germany and reflects in terms of a Polanyian double movement on how far care and care work – in the case of elder and child care and, more precisely, home care agencies, residential care communities and the social investment state – have become a contested terrain. The third part, the conclusion, points out how tendencies like the economic shift touch care and care work.
Sociology
Keywords: Giro económico; Virage économique; agence de soins à domicile; agencias de atención a domicilio; atención a los mayores y la infancia; capitalism; care work; communautés de soin; comunidades de atención; corporate reorganizations; doble movimiento; double movement; doublé mouvement; economic shift; elder and child care; home care agencies; inversión social; investissement social; reproducción social; reproduction sociale; residential care communities and social investment; social reproduction; social services; socioeconomics; soin aux personnes âgées et à l’enfance

Permanenter Notstand und der Kampf um gute Sorge(arbeit) – Polanyi’sche Doppelbewegungen in der Marktgesellschaft - Décieux, Fabienne; Becker, Karina; Kutlu, Yalcin (Industrielle Beziehungen, 2020)
Der Artikel untersucht kollektives Interessenhandeln in der (Klein-)Kinderbetreuung in Deutschland und Österreich. Mit der Polanyi’schen Figur der Doppelbewegung werden die Dynamiken der aktuellen Aushandlungen im Feld der Sorge und Sorgearbeit aufeinander bezogen und analytisch gefasst. Die Bewegung in Form einer (Quasi-)Vermarktlichung steht im Spannungsverhältnis zum ausgeprägten Berufsethos der ErzieherInnen, um das sie durch Proteste (Österreich) und Streiks (Deutschland) kämpfen.
Publisher: Verlag Barbara Budrich
Keywords: (Early) Child care; (Klein-)Kinderbetreuung; (Quasi-)Vermarktlichung; (quasi) marketization; D63; Industrial Relations. JEL: B54; Industrielle Beziehungen; J81; Polanyi; Sorgearbeit; care work

Capitalism in Transformation: Movements and Countermovements in the 21st Century - Atzmüller, Roland; Aulenbacher, Brigitte; Brand, Ulrich; Décieux, Fabienne; Fischer, Karin; Sauer, Birgit (Edward Elgar Publishing, 2019)
Presenting a profound and far-reaching analysis of economic, ecological, social, cultural and political developments of contemporary capitalism, this book draws on the work of Karl Polanyi, and re-reads it for our times. The renowned authors offer key insights to current changes in the relations between the economy, politics and society, and their ecological and social effects.
Sociology
Keywords: biography; capitalism; countermovement; fictitious commodities